Synthesis of New Nucleoside Analogues from Theobromine - Al-Mouamin, Thanaa M; Abid, Sumaya J (Al-Nahrain Journal of Science, 2019)
Nucleoside Analogues play important role in different medical drugs,therefor we synthesized new nucleoside analogues using theobromine as a nucleobase, for the first time, by convertion to it's mercury salt, [1]. Then coupled with three kinds of sugar, including (glucose, galactose and mannose), after protection [2-4] and activation as bromo sugar [5-7] afforded blocked nucleoside analogues [8-10] which subsequently hydrolyzed to give our synthetic goal the free nucleoside analogues [11-13]. All prepared compounds were identify by FT-IR and some of them with 1H-NMR spectroscopy. The synthesized compounds (11-13) were screened for their in-vitro antibacterial and antifungal activity.